Operationalizing Contemporary Istiḥsān: A Methodological Framework for Navigating Innovation in Capital and Digital Markets - Husni; Yengkie Hirawan; Musda Asmara; Naim Mathlouthi; Rohmah Maulidia; Hani Mefleh O. Hamdon (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
The application of istiḥsān in the digital economy continues to face challenges related to subjectivity and the lack of methodological transparency. This study aims to formulate a seven-stage istiḥsān operational model as a structured framework for enhancing accountability in Sharia economic legal reasoning. Employing a critical juridical-normative approach grounded in legal coherence theory, the proposed model provides objective criteria to guide mujtahids in determining exceptional legal rulings. The model was validated through two strategic case studies: (1) a retrospective analysis of Sukuk instruments and (2) a prospective analysis of Non-Fungible Tokens (NFTs). The findings demonstrate that the model successfully reconstructs the implicit legal reasoning underlying established Sukuk fatwas, thereby confirming its retrospective consistency. Prospectively, when applied to NFTs, the model functions as a rigorous evaluative filter that permits innovation only when the anticipated maṣlaḥah outweighs the potential mafsadah. In cases where secondary harms—such as the environmental costs associated with energy consumption and speculative market bubbles—predominate, the model justifies restricting such innovations. This study makes a significant academic contribution by transforming contemporary istiḥsān from an abstract jurisprudential concept into a replicable, transparent, and auditable analytical framework. It demonstrates that structured ijtihād provides a robust governance mechanism for fostering ethical, accountable, and sustainable Sharia-compliant innovation in global capital markets.